Steroidogenic pathway in girls diagnosed with autism spectrum disorders - Jansakova, Katarina; Hill, Martin; Celusakova, Hana; Repiska, Gabriela; Bicikova, Marie; Macova, Ludmila; Polonyiova, Katarína; Kopcikova, Mária; Ostatnikova, Daniela (PloS one, 2024)
The diagnostic prevalence of autism spectrum disorders (ASD) shows boys to be more affected than girls. Due to this reason, there is a lack of research including and observing ASD girls. Present study was aimed to detect hormones of steroidogenesis pathway in prepubertal girls (n = 16) diagnosed with ASD and sex and age matched neurotypical controls (CTRL, n = 16). Collected plasma served for detection of conjugated and unconjugated steroids using gas chromatography tandem-mass spectrometry. We observed higher levels of steroids modulating ionotropic receptors, especially, GABAergic steroids and pregnenolone sulfate in ASD group. Concentration of many steroids throughout the pathway tend to be higher in ASD girls compared to CTRL. Pregnenolone and its isomers together with polar progestins and androstanes, i.e. sulfated steroids, were found to be higher in ASD group in comparison with CTRL group. Based on steroid product to precursor ratios, ASD group showed higher levels of sulfated/conjugated steroids suggesting higher sulfotransferase or lower steroid sulfatase activity and we also obtained data indicating lower activity of steroid 11β-hydroxylase compared to CTRL group despite higher corticosterone level observed in ASD. These findings need to be generalized in future studies to examine both genders and other age groups.
Keywords: poruchy autistického spektra; Humans; Case-Control Studies; dítě; studie případů a kontrol; Child; Autism Spectrum Disorder; Female; lidé; pregnenolon; steroidy; předškolní dítě; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Male; Gas Chromatography-Mass Spectrometry; mužské pohlaví; Steroids; Child, Preschool; Pregnenolone